Mujadalah bil Lati Hiya Ahsan - salmadanis salmadanis (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2004)
There are two mujadalah forms, they are al-su'i mujadalah and ahsan mujadalah. Ahsan Mujadalah likely can be translated with better discussing for fjnding the truth, passing ideas exchange, or in communications with two ways comunicdion, that is happened between commwnicator with audience. The writer explains the discourse of this terminology